Integrated Customer-Focused Knowledge Portals: Design Challenges and Empirical Approaches - Claudia Löbbecke; Kevin Crowston; Nicolas Friederici (Academy of Management Conference, OCIS Division, 2011)
Knowledge Portals (KPs) are highly integrative Knowledge Management Systems (KMS) that promise to synthesize widely dispersed knowledge and to interconnect individuals by functioning as a 'one-stop knowledge shop'. Yet, in practice, KPs face major challenges, which are for the most part due to the intricacies of knowledge exchange being subjected to multi-faceted individual and social factors. At the same time, growing anecdotal evidence from case studies indicates KPs' enormous potential. This paper makes an effort to more distinctly conceptualize KPs and emphasize a KP's role to unify networking and repository KMS features. The paper develops three major challenges to successful KP deployment, namely (1) knowledge integration, (2) sufficient participation, and (3) favorable organizational culture and validates these as applicable to KP through a review of 42 empirical papers. The paper concludes with suggestions towards a set of design principles for KP.